Peranan Indonesia Dalam Mewujudkan Keamanan Maritim Di Kawasan Asean - Dayu Medina; Dewi Enggriyeni (Faculty of Law, Andalas University, 2022)
United Nation Convention Law of The Sea (UNCLOS 1982) regulates maritime boundaries, rights and obligations of coastal states, and maritime security. This article aims to find out about how the role of Indonesia to realize maritime security in ASEAN areas. Maritime security is one of the important things that must be created in ASEAN, because this region is dominated by oceans. Indonesia as the largest archipolegic caountry in ASEAN have a role to create maritime security. This paper is to find out how is ASEAN policies in creating maritime security in the ASEAN and to find out what is the role of Indonesia to realizing maritime security in the ASEAN. The method used in this article is the normative method so that this assessment will provide an explanation of Indonesia’s role in realizing maritime security in the ASEAN, either by initiating international forum, or participating in existing maritime international forum, and make regulations for their own country, because Indonesia is one of the counties with largest number of crime at sea in ASEAN.